Anti-hydrolysis aluminum nitride granulation powder and preparation method thereof

Through the ball mill mixing technology of polyethylene glycol, yttrium oxide and silane coupling agent, combined with spray granulation, the problem of uneven packaging of large-sized aluminum nitride granulation powder against hydrolytic layer is solved, and its anti-hydrolysis performance is significantly improved. Performance of ceramic structural parts.

CN119161192APending Publication Date: 2024-12-20CHALCO SHANDONG CO LTD

Patent Information

Application Number
CN202411367653.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The prior art is difficult to achieve uniform and fixed hydrolysis-resistant layer wrapping in large-sized aluminum nitride granulated powder, resulting in hydrolysis of aluminum nitride in wet air, affecting the thermal conductivity and bending strength of ceramic substrates and structural parts.

Method used

Polyethylene glycol, yttrium oxide and organic solvents are used for ball milling and mixing, combining silane coupling agent and adhesive, and spherical anti-hydrolyzed aluminum nitride granulation powder is prepared through spray granulation technology to ensure uniform dispersion and bonding, and improve resistance. Hydrolysis properties.

Benefits of technology

The uniform hydrolysis layer wrapping of aluminum nitride granulated powder is achieved, which significantly improves its hydrolysis resistance, extends the hydrolysis time, and ensures high thermal conductivity and bending strength in ceramic structural parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161192A_ABST
    Figure CN119161192A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of aluminum nitride powder preparation, in particular to hydrolysis-resistant aluminum nitride granulation powder and a preparation method thereof. The preparation method comprises the following steps: carrying out first ball-milling mixing on polyethylene glycol, yttrium oxide and an organic solvent to obtain a first mixture; aluminum nitride powder, a silane coupling agent and the first mixture are subjected to second ball milling mixing, and a second mixture is obtained; performing third ball-milling mixing on an adhesive and the second mixture to obtain mixed slurry; screening the mixed slurry to obtain a filtered material; carrying out spray granulation on the filtered material to obtain spherical hydrolysis-resistant aluminum nitride granulation powder; the second ball-milling mixing time > the third ball-milling mixing time > the first ball-milling mixing time. According to the preparation method, soft agglomeration of the aluminum nitride powder can be depolymerized through ball-milling mixing modification, in addition, in the ball-milling mixing process, grinding balls can collide with the aluminum nitride powder to generate energy, so that a silane coupling agent is anchored on the surfaces of aluminum nitride powder particles, and the hydrolysis resistance of the aluminum nitride powder is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of aluminum nitride powder preparation, and in particular to a hydrolysis-resistant aluminum nitride granulated powder and a preparation method thereof. Background Art

[0002] Aluminum nitride (AlN) is a semiconductor ceramic material with the advantages of high thermal conductivity, low dielectric constant, high electrical insulation, high temperature resistance, non-toxicity, and a thermal expansion coefficient matching that of silicon. It is considered to be a key material for semiconductor substrates and device packaging. However, aluminum nitride is very easy to hydrolyze in humid air to generate aluminum oxide compounds and ammonia. The generated aluminum oxide compounds will cover the surface of aluminum nitride, which will greatly reduce the thermal conductivity of aluminum nitride. In the process of using this type of hydrolyzed aluminum nitride as a raw material to prepare ceramic substrates and ceramic structural parts, especially under high-temperature calcination, the aluminum oxide compounds on the surface of the hydrolyzed aluminum nitride will decompose into aluminum oxide. The generated aluminum oxide will undergo a crystal transformation at different temperatures, thereby affecting the thermal conductivity, density and bending strength of the ceramic substrate and ceramic structural parts.

[0003] There are many studies on the hydrolysis resistance of aluminum nitride, but these methods either require high-temperature treatment or water bath stirring, and are mainly applied to aluminum nitride raw powder or aluminum nitride thermal conductive powder with high particle strength. However, as a key raw material for the manufacture of large-sized aluminum nitride structural parts, aluminum nitride granulated powder is a pseudo-secondary particle that is formed by bonding primary particles into agglomerates with an organic binder. The strength of the obtained aluminum nitride granulated powder particles is weak, and there are gaps in the primary particles during the bonding process. The specific surface area of ​​the primary particles is high and it is very easy to hydrolyze. Although it is currently possible to use surface modification methods to cover the surface of aluminum nitride with an anti-hydrolysis layer, this anti-hydrolysis layer cannot evenly and fixedly wrap the aluminum nitride granulated powder, which ultimately affects the anti-hydrolysis performance of aluminum nitride.

[0004] At present, there are many studies on the hydrolysis resistance of aluminum nitride, mainly including the following methods: (1) High-temperature heat treatment method: Aluminum nitride is placed in an oxidizing atmosphere, and by controlling the oxygen content, oxidation temperature and time, the surface of aluminum nitride is oxidized to form a dense aluminum oxide film, thereby hindering the further reaction of aluminum nitride with water. (2) Inorganic acid method: Aluminum nitride is mixed with a certain concentration of phosphoric acid-aluminum dihydrogen phosphate aqueous solution to form a passivation film on the surface of aluminum nitride, thereby achieving the purpose of hydrolysis resistance. (3) Surface coating method: Silane coupling agent, titanate coupling agent, etc. are stirred and coated with aluminum nitride and anhydrous ethanol at a certain temperature, and after filtering and drying, organic surface-coated aluminum nitride can be obtained. Summary of the invention

[0005] The present application provides a hydrolysis-resistant aluminum nitride granulated powder and a preparation method thereof to solve the following technical problem: how to improve the uniformity and fixation degree of the aluminum nitride granulated powder coated with an anti-hydrolysis layer.

[0006] In a first aspect, the present application provides a method for preparing hydrolysis-resistant aluminum nitride granulated powder, the preparation method comprising:

[0007] Performing a first ball milling to mix polyethylene glycol, yttrium oxide and an organic solvent to obtain a first mixture;

[0008] Performing a second ball milling mixing of aluminum nitride powder, silane coupling agent and the first mixture to obtain a second mixture;

[0009] The binder and the second mixture are mixed by a third ball milling process to obtain a mixed slurry;

[0010] Screening the mixed slurry to obtain a filtrate;

[0011] The filtered material is subjected to spray granulation to obtain spherical hydrolysis-resistant aluminum nitride granulated powder;

[0012] The rotation speeds of the first ball milling, the second ball milling and the third ball milling are 5 rpm to 10 rpm respectively, and the time of the second ball milling>the time of the third ball milling>the time of the first ball milling.

[0013] Optionally, the first ball milling mixing time is 2 h to 4 h, the second ball milling mixing time is 30 h to 50 h, and the third ball milling mixing time is 8 h to 12 h.

[0014] Optionally, the grinding media used for the first ball milling mixture, the second ball milling mixture and the third ball milling mixture include a first grinding medium, a second grinding medium and a third grinding medium, respectively, the particle size of the first grinding medium is 37 mm to 43 mm, the particle size of the second grinding medium is 27 mm to 33 mm, and the particle size of the third grinding medium is 17 mm to 23 mm.

[0015] Optionally, the weight m1 of the first grinding medium, the weight m2 of the second grinding medium and the weight m3 of the third grinding medium satisfy the relationship: m1:m2:m3=(16-18):(11-13):(8-10).

[0016] Optionally, the weight m4 of the polyethylene glycol, the weight m5 of the yttrium oxide and the weight m6 of the organic solvent satisfy the relationship: m4:m5:m6=(0.15-0.18):(2.5-3.0):(31-44).

[0017] Optionally, the total weight m7 of the aluminum nitride powder, the weight m8 of the silane coupling agent and the weight m9 of the adhesive satisfy the relationship: m7:m8:m9=(50-60):(1.5-2.4):(1.5-3.6).

[0018] Optionally, the silane coupling agent includes at least one of the following:

[0019] KH-580 coupling agent, XY-565 coupling agent and XY-350 coupling agent; and / or

[0020] The organic solvent includes anhydrous ethanol; and / or,

[0021] The adhesive includes polyvinyl butyral.

[0022] Optionally, the particle size D50 of the aluminum nitride powder is 1 μm to 2 μm, and the weight content m10 of oxygen in the aluminum nitride and the total weight m7 of the aluminum nitride powder satisfy the relationship: m10:m7<1:100.

[0023] Optionally, the viscosity of the mixed slurry is 60 cP to 200 cP.

[0024] In a second aspect, the present application provides a hydrolysis-resistant aluminum nitride granulated powder, which is prepared by the preparation method described in the first aspect.

[0025] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0026] The present application provides a method for preparing a hydrolysis-resistant aluminum nitride granulated powder. The method first disperses yttrium oxide in polyethylene glycol and an organic solvent by a first ball milling mixing method to obtain a uniformly dispersed first mixture, and then mixes aluminum nitride powder, a silane coupling agent and the first mixture by a second ball milling mixing method. The second ball milling mixing method causes strong collision between the aluminum nitride powder, the silane coupling agent and the first mixture, and fully deagglomerates the soft agglomerated aluminum nitride powder. The fully deagglomerated aluminum nitride powder can be uniformly combined with the polyethylene glycol in the first mixture, so that the aluminum nitride powder and the yttrium oxide are uniformly dispersed, so as to maintain the primary particle state of the aluminum nitride powder, thereby improving the uniformity of the aluminum nitride powder and obtaining a uniform distribution of each substance. The second mixture of the cloth is prepared, and then the aluminum nitride powder and yttrium oxide in the adhesive and the second mixture are firmly bonded by the third ball milling mixing method, and finally spherical hydrolysis-resistant aluminum nitride granulated powder is obtained; in addition, the rotation speeds of the first ball milling mixing, the second ball milling mixing and the third ball milling mixing can be 5rpm-10rpm respectively, and the time of the second ball milling mixing is greater than the time of the third ball milling mixing and greater than the time of the first ball milling mixing. During the second ball milling mixing, the silane coupling agent can be firmly anchored on the particle surface of the aluminum nitride powder that maintains the primary particle state, so that a complete anti-hydrolysis layer is coated on the particle surface of the aluminum nitride powder, and the fixing degree of the anti-hydrolysis layer on the surface of the aluminum nitride powder is improved, thereby improving the anti-hydrolysis performance of the aluminum nitride powder. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0028] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0029] Figure 1 A schematic flow chart of a method for preparing hydrolysis-resistant aluminum nitride granulated powder provided in an embodiment of the present application. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0031] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within the range; for example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range; in addition, whenever a numerical range is indicated in this document, it is meant to include any cited numbers (fractions or integers) within the indicated range.

[0032] In this document, the terms including "comprising" and the like mean "including but not limited to". Relational terms such as "first" and "second" are merely used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. "And / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone; wherein A and B can be singular or plural. Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased on the market or prepared by existing methods.

[0033] It should be noted that, with respect to the prior art (1) recorded in the background technology, the inventor found that: when using sealed packaging, it is necessary to introduce nitrogen into the sealed packaging for protection, which requires the introduction of packaging equipment with a complex structure, and the nitrogen in the sealed packaging is prone to leakage. The sealed packaging that leaks nitrogen is bound to have the problem of hydrolysis of aluminum nitride granulated powder. With respect to the prior art (2) recorded in the background technology, the inventor found that: when using an oven for storage, the oven storage wastes electricity and space, and will also increase the production cost of aluminum nitride ceramic structural parts. With respect to the prior art (3) recorded in the background technology, the inventor found that: using the surface modification method to cover the surface of aluminum nitride with an anti-hydrolysis layer, but this anti-hydrolysis layer cannot evenly and fixedly wrap the aluminum nitride granulated powder, which ultimately affects the anti-hydrolysis performance of aluminum nitride.

[0034] Figure 1 The schematic diagram of the process of preparing a hydrolysis-resistant aluminum nitride granulated powder provided in an embodiment of the present application is exemplarily shown;

[0035] like Figure 1 As shown, the present application embodiment provides a method for preparing hydrolysis-resistant aluminum nitride granulated powder, the preparation method comprising:

[0036] S1. The polyethylene glycol, yttrium oxide and the organic solvent are first ball-milled to obtain a first mixture;

[0037] S2. The aluminum nitride powder, the silane coupling agent and the first mixture are mixed by a second ball milling to obtain a second mixture;

[0038] S3. The binder and the second mixture are mixed by a third ball mill to obtain a mixed slurry;

[0039] S4. Screening the mixed slurry to obtain a filtrate;

[0040] S5. The filtrate is spray granulated to obtain a spherical hydrolysis-resistant aluminum nitride granulated powder;

[0041] The rotation speeds of the first ball milling, the second ball milling and the third ball milling are 5 rpm to 10 rpm respectively, and the time of the second ball milling>the time of the third ball milling>the time of the first ball milling.

[0042] The rotation speeds of the first ball milling, the second ball milling and the third ball milling can be 5 rpm, 6 rpm, 7 rpm, 8 rpm, 9 rpm or 10 rpm respectively.

[0043] It should be noted that the screening can use a 100# stainless steel sieve, which can separate the large particles that are not completely dissolved in the mixed slurry.

[0044] It should be noted that the spray granulation can be carried out using a closed centrifugal granulation tower.

[0045] It should be noted that the yttrium oxide may be yttrium oxide with a purity of more than 99.999%, and the particle size of the yttrium oxide is ≤50nm.

[0046] In some optional embodiments, the first ball milling mixing time is 2h to 4h, the second ball milling mixing time is 30h to 50h, and the third ball milling mixing time is 8h to 12h;

[0047] In these embodiments, the first ball milling mixing time can be 2h~4h, and yttrium oxide is dispersed into polyethylene glycol and organic solvent by the first ball milling mixing method to obtain a uniformly dispersed first mixture; in addition, the second ball milling mixing time can be 30h~50h, and the strong collision between aluminum nitride powder, silane coupling agent and the first mixture is performed by the second ball milling mixing method, so that the soft agglomerated aluminum nitride powder is fully depolymerized, and the fully depolymerized aluminum nitride powder can be uniformly combined with the polyethylene glycol in the first mixture, so that the aluminum nitride powder and yttrium oxide are uniformly dispersed to maintain the primary particle state of the aluminum nitride powder, thereby improving the uniformity of the aluminum nitride powder and obtaining a second mixture in which each substance is uniformly distributed; in addition, the third ball milling mixing time can be 8h~12h, and the adhesive and the aluminum nitride powder and yttrium oxide in the second mixture are firmly bonded by the third ball milling mixing method, and finally spherical hydrolysis-resistant aluminum nitride granulated powder is obtained.

[0048] The first ball milling mixing time can be 2 h, 2.5 h, 3.0 h, 3.5 h or 4.0 h.

[0049] The second ball milling mixing time can be 30 h, 35 h, 40 h, 45 h or 50 h.

[0050] The third ball milling mixing time can be 8 h, 9 h, 10 h, 11 h or 12 h.

[0051] In some optional embodiments, the grinding media used in the first ball milling, the second ball milling and the third ball milling respectively include a first grinding medium, a second grinding medium and a third grinding medium, the particle size of the first grinding medium is 37 mm to 43 mm, the particle size of the second grinding medium is 27 mm to 33 mm, and the particle size of the third grinding medium is 17 mm to 23 mm;

[0052] In these embodiments, the grinding media used for the first ball milling, the second ball milling and the third ball milling can include the first grinding medium, the second grinding medium and the third grinding medium, respectively, and the particle size of the first grinding medium can be 37 mm to 43 mm, the particle size of the second grinding medium can be 27 mm to 33 mm, and the particle size of the third grinding medium can be 17 mm to 23 mm, so that the first grinding medium, the second grinding medium and the third grinding medium have sufficiently fine particle sizes, and the first grinding medium is used to promote the first ball milling to be fully carried out, and yttrium oxide is dispersed in polyethylene glycol and organic solvent to obtain a uniformly dispersed first mixture; the second ball milling is promoted to be fully carried out by the second grinding medium, and the strong collision between aluminum nitride powder, silane coupling agent and the first mixture fully deagglomerates the soft agglomerated aluminum nitride powder, so as to obtain a second mixture in which each substance is evenly distributed; the third ball milling is promoted to be fully carried out by the third grinding medium, and the aluminum nitride powder and yttrium oxide in the adhesive and the second mixture are firmly bonded to obtain spherical hydrolysis-resistant aluminum nitride granulated powder.

[0053] The particle size of the first grinding medium can be 37 mm, 38 mm, 39 mm, 40 mm, 41 mm, 42 mm or 43 mm.

[0054] The particle size of the second grinding medium can be 27 mm, 28 mm, 29 mm, 30 mm, 31 mm, 32 mm or 33 mm.

[0055] The particle size of the third grinding medium can be 17 mm, 18 mm, 19 mm, 20 mm, 21 mm, 22 mm or 23 mm.

[0056] In some optional embodiments, the weight m1 of the first grinding medium, the weight m2 of the second grinding medium, and the weight m3 of the third grinding medium satisfy the relationship: m1:m2:m3=(16-18):(11-13):(8-10);

[0057] In these embodiments, the weight m1 of the first grinding medium, the weight m2 of the second grinding medium and the weight m3 of the third grinding medium can satisfy the relationship: m1:m2:m3=(16-18):(11-13):(8-10), which promotes the first ball milling mixing, the second ball milling mixing and the third ball milling mixing to be fully carried out to obtain spherical hydrolysis-resistant aluminum nitride granulated powder.

[0058] The weight m1 of the first grinding medium, the weight m2 of the second grinding medium and the weight m3 of the third grinding medium can satisfy the relationship: m1:m2:m3=16:11:8, 16:11:9, 16:11:10, 16:12:8, 16:12:9, 16:12:10, 16:13:8, 16:13:9, 16:13:10, 17:11:8, 17: 11:9, 17:11:10, 17:12:8, 17:12:9, 17:12:10, 17:13:8, 17:13:9, 17:13:10, 18:11:8, 18:11:9, 18:11:10, 18:12:8, 18:12:9, 18:12:10, 18:13:8, 18:13:9 or 18:13:10.

[0059] In some optional embodiments, the weight m4 of the polyethylene glycol, the weight m5 of the yttrium oxide and the weight m6 of the organic solvent satisfy the relationship: m4:m5:m6=(0.15-0.18):(2.5-3.0):(31-44);

[0060] In these embodiments, the weight m4 of polyethylene glycol, the weight m5 of yttrium oxide and the weight m6 of the organic solvent satisfy the relationship: m4:m5:m6=(0.15-0.18):(2.5-3.0):(31-44). Yttrium oxide can be dispersed in the polyethylene glycol and the organic solvent by the first ball milling mixing method, thereby obtaining a uniformly dispersed first mixture.

[0061] The weight m4 of the polyethylene glycol, the weight m5 of the yttrium oxide and the weight m6 of the organic solvent satisfy the relationship: m4:m5:m6=0.15:2.5:31, 0.15:2.5:35, 0.15:2.5:40, 0.15:2.5:44, 0.15:2.7:31, 0.15:2.7:35, 0.15:2.7:40, 0.15:2.7:44, 0.15:3.0:31, 0.15:3.0:35, 0.15:3.0:40, 0.15:3.0:44, 0.16:2.5:31, 0.16:2.5:35, 0.16:2.5:40, 0.16:2.5:44, 0. 0.18:2.7:31, 0.16:2.7:35, 0.16:2.7:40, 0.16:2.7:44, 0.16:3.0:31, 0.16:3.0:35, 0.16:3.0:40, 0.16:3.0:44, 0.18:2.5:31, 0.18:2.5:35, 0.18:2.5:40, 0.18:2.5:44, 0.18:2.7:31, 0.18:2.7:35, 0.18:2.7:40, 0.18:2.7:44, 0.18:3.0:31, 0.18:3.0:35, 0.18:3.0:40, or 0.18:3.0:44.

[0062] In some optional embodiments, the total weight m7 of the aluminum nitride powder, the weight m8 of the silane coupling agent, and the weight m9 of the adhesive satisfy the relationship: m7:m8:m9=(50-60):(1.5-2.4):(1.5-3.6);

[0063] In these embodiments, the total weight m7 of the aluminum nitride powder, the weight m8 of the silane coupling agent, and the weight m9 of the adhesive satisfy the relationship: m7:m8:m9=(50-60):(1.5-2.4):(1.5-3.6). The second ball milling mixing causes a strong collision between the aluminum nitride powder, the silane coupling agent, and the first mixture, and the soft agglomerated aluminum nitride powder is fully deagglomerated to maintain the primary particle state of the aluminum nitride powder, thereby improving the uniformity of the aluminum nitride powder. In addition, the adhesive and the aluminum nitride powder and yttrium oxide in the second mixture are firmly bonded by the third ball milling mixing, and finally spherical hydrolysis-resistant aluminum nitride granulated powder is obtained.

[0064] The total weight m7 of the aluminum nitride powder, the weight m8 of the silane coupling agent and the weight m9 of the adhesive satisfy the relationship: m7:m8:m9=50:1.5:1.5, 50:1.5:2.0, 50:1.5:2.5, 50:1.5:3.0, 50:1.5:3.6, 50:2.0:1.5, 50:2.0:2.0, 50:2.0:2.5, 5 0:2.0:3.0, 50:2.0:3.6, 50:2.4:1.5, 50:2.4:2.0, 50:2.4:2.5, 50:2.4:3.0, 50:2.4:3.6, 55:1.5:1.5, 55:1.5:2.0, 55:1.5:2.5, 55:1.5:3.0, 55:1.5:3.6, 55:2 .0:1.5, 55:2.0:2.0, 55:2.0:2.5, 55:2.0:3.0, 55:2.0:3.6, 55:2.4:1.5, 55:2.4:2.0, 55:2.4:2.5, 55:2.4:3.0, 55:2.4:3.6, 60:1.5:1.5, 60:1.5:2.0, 60:1.5: or 60:2.4:3.6.

[0065] In some optional embodiments, the silane coupling agent includes at least one of the following:

[0066] KH-580 coupling agent, XY-565 coupling agent and XY-350 coupling agent; and / or

[0067] The organic solvent includes anhydrous ethanol; and / or,

[0068] The adhesive includes polyvinyl butyral;

[0069] In these embodiments, the silane coupling agent may include: at least one of KH-580 coupling agent, XY-565 coupling agent and XY-350 coupling agent, which may cover most of the silane coupling agents, and the silane coupling agent is firmly anchored on the particle surface of the aluminum nitride powder that maintains the primary particle state, so as to coat a complete anti-hydrolysis layer on the particle surface of the aluminum nitride powder, and improve the fixation degree of the anti-hydrolysis layer on the surface of the aluminum nitride powder, thereby improving the anti-hydrolysis performance of the aluminum nitride powder; in addition, the organic solvent may include anhydrous ethanol, and the anhydrous ethanol may be used to fully disperse polyethylene glycol, so that the polyethylene glycol is evenly dispersed on the surface of the aluminum nitride powder, so as to maintain the primary particle state of the aluminum nitride powder and improve the uniformity of the aluminum nitride powder; in addition, the adhesive may include polyvinyl butyral, and the yttrium oxide and the second mixture are fully combined by the polyvinyl butyral, and finally a spherical anti-hydrolysis aluminum nitride granulated powder is obtained.

[0070] In some optional embodiments, the particle size D50 of the aluminum nitride powder is 1 μm to 2 μm, and the weight content m10 of oxygen in the aluminum nitride and the total weight m7 of the aluminum nitride powder satisfy the relationship: m10:m7<1:100;

[0071] In these embodiments, the particle size D50 of the aluminum nitride powder can be 1 μm to 2 μm, and the weight content m10 of oxygen in the aluminum nitride and the total weight m7 of the aluminum nitride powder can satisfy the relationship: m10:m7<1:100, which can enable the aluminum nitride powder to have a sufficiently large specific surface area to facilitate the silane coupling agent to be firmly anchored on the particle surface of the aluminum nitride powder, so that a complete anti-hydrolysis layer can be coated on the particle surface of the aluminum nitride powder, and the fixation degree of the anti-hydrolysis layer on the surface of the aluminum nitride powder can be improved.

[0072] The particle size D50 of the aluminum nitride powder may be 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm or 2.0 μm.

[0073] In some optional embodiments, the viscosity of the mixed slurry is 60 cP to 200 cP;

[0074] In these embodiments, the viscosity of the mixed slurry may be 60 cP to 200 cP, so that the mixed slurry has sufficient viscosity. The mixed slurry with sufficient viscosity can facilitate subsequent spray drying to ultimately obtain spherical hydrolysis-resistant aluminum nitride granulated powder with ideal morphology.

[0075] The viscosity of the mixed slurry may be 60 cP, 80 cP, 100 cP, 120 cP, 140 cP, 160 cP, 180 cP or 200 cP.

[0076] It should be noted that the viscosity of the mixed slurry was measured at 30°C.

[0077] Based on a general inventive concept, an embodiment of the present application provides a hydrolysis-resistant aluminum nitride granulated powder, and the hydrolysis-resistant aluminum nitride granulated powder is prepared by the preparation method.

[0078] The hydrolysis-resistant aluminum nitride granulated powder is obtained by the above-mentioned preparation method. The specific steps of the preparation method can refer to the above-mentioned embodiment. Since the hydrolysis-resistant aluminum nitride granulated powder adopts part or all of the technical solutions of the above-mentioned embodiment, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be repeated here one by one.

[0079] The present application is further described below in conjunction with specific examples. The experimental methods in the following examples that do not specify specific conditions are usually measured according to industry standards; if there are no corresponding industry standards, they are carried out according to common international standards, conventional conditions, or conditions recommended by the manufacturer.

[0080] Example 1

[0081] like Figure 1 As shown, a method for preparing hydrolysis-resistant aluminum nitride granulated powder comprises:

[0082] S1. The polyethylene glycol, yttrium oxide and the organic solvent are first ball-milled to obtain a first mixture;

[0083] S2. The aluminum nitride powder, the silane coupling agent and the first mixture are mixed by a second ball milling to obtain a second mixture;

[0084] S3. The binder and the second mixture are mixed by a third ball mill to obtain a mixed slurry;

[0085] S4. Screening the mixed slurry to obtain a filtrate;

[0086] S5. The filtrate is spray granulated to obtain a spherical hydrolysis-resistant aluminum nitride granulated powder;

[0087] The rotation speed of the first ball milling mixing is 10 rpm, the rotation speed of the second ball milling mixing is 10 rpm, and the rotation speed of the third ball milling mixing is 10 rpm; the time of the first ball milling mixing is 2 h, the time of the second ball milling mixing is 30 h, and the time of the third ball milling mixing is 8 h.

[0088] The grinding media used in the first ball milling, the second ball milling and the third ball milling respectively include the first grinding medium, the second grinding medium and the third grinding medium, the particle size of the first grinding medium is 40 mm, the particle size of the second grinding medium is 30 mm, and the particle size of the third grinding medium is 20 mm.

[0089] The weight m1 of the first grinding medium, the weight m2 of the second grinding medium, and the weight m3 of the third grinding medium satisfy the relationship: m1:m2:m3=16:11:8.

[0090] The weight m4 of polyethylene glycol, the weight m5 of yttrium oxide and the weight m6 of the organic solvent satisfy the relationship:

[0091] m4:m5:m6=0.15:2.5:43.85.

[0092] The total weight m7 of the aluminum nitride powder, the weight m8 of the silane coupling agent, and the weight m9 of the adhesive satisfy the relationship:

[0093] m7:m8:m9=50:1.5:2.0.

[0094] The silane coupling agent is KH-580 type coupling agent;

[0095] Organic solvents include anhydrous ethanol;

[0096] The adhesive includes polyvinyl butyral.

[0097] The particle size D50 of the aluminum nitride powder is 1.0 μm to 2.0 μm, and the weight content m10 of oxygen in the aluminum nitride and the total weight m7 of the aluminum nitride powder satisfy the relationship: m10:m7<1:100.

[0098] The viscosity of the mixed slurry was 68 cP.

[0099] The invention discloses hydrolysis-resistant aluminum nitride granulated powder, which is prepared by a preparation method.

[0100] Example 2

[0101] Based on the contents disclosed in Example 1, the following modifications are further made:

[0102] The rotation speed of the first ball milling mixing was 5 rpm, the rotation speed of the second ball milling mixing was 5 rpm, and the rotation speed of the third ball milling mixing was 5 rpm.

[0103] The weight m1 of the first grinding medium, the weight m2 of the second grinding medium, and the weight m3 of the third grinding medium satisfy the relationship: m1:m2:m3=18:13:10.

[0104] The viscosity of the mixed slurry was 74 cP.

[0105] Example 3

[0106] Based on the contents disclosed in Example 1, the following modifications are further made:

[0107] The rotation speed of the first ball milling mixing is 5 rpm, the rotation speed of the second ball milling mixing is 5 rpm, and the rotation speed of the third ball milling mixing is 5 rpm; the time of the first ball milling mixing is 3 h, the time of the second ball milling mixing is 40 h, and the time of the third ball milling mixing is 10 h.

[0108] The weight m4 of polyethylene glycol, the weight m5 of yttrium oxide and the weight m6 of the organic solvent satisfy the relationship:

[0109] m4:m5:m6=0.165:2.75:37.135.

[0110] The total weight m7 of the aluminum nitride powder, the weight m8 of the silane coupling agent, and the weight m9 of the adhesive satisfy the relationship:

[0111] m7:m8:m9=55:2.2:2.75.

[0112] The silane coupling agent is XY-565 type coupling agent.

[0113] The viscosity of the mixed slurry was 127 cP.

[0114] Example 4

[0115] Based on the contents disclosed in Example 1, the following modifications are further made:

[0116] The first ball milling mixing time was 4 h, the second ball milling mixing time was 50 h, and the third ball milling mixing time was 12 h.

[0117] The weight m1 of the first grinding medium, the weight m2 of the second grinding medium, and the weight m3 of the third grinding medium satisfy the relationship: m1:m2:m3=18:13:10.

[0118] The weight m4 of polyethylene glycol, the weight m5 of yttrium oxide and the weight m6 of the organic solvent satisfy the relationship:

[0119] m4:m5:m6=0.18:3.0:30.82.

[0120] The total weight m7 of the aluminum nitride powder, the weight m8 of the silane coupling agent, and the weight m9 of the adhesive satisfy the relationship:

[0121] m7:m8:m9=60:2.4:3.6.

[0122] The silane coupling agent is XY-350 type coupling agent.

[0123] The viscosity of the mixed slurry was 189 cP.

[0124] Example 5

[0125] Based on the contents disclosed in Example 1, the following modifications are further made:

[0126] The rotation speed of the first ball milling mixing was 7 rpm, the rotation speed of the second ball milling mixing was 7 rpm, and the rotation speed of the third ball milling mixing was 7 rpm.

[0127] The weight m1 of the first grinding medium, the weight m2 of the second grinding medium, and the weight m3 of the third grinding medium satisfy the relationship: m1:m2:m3=17:12:9.

[0128] Comparative Example 1

[0129] Based on the contents disclosed in Example 1, the following modifications are further made:

[0130] No adhesive is added.

[0131] The rotation speed of the first ball milling mixing is 5 rpm, the rotation speed of the second ball milling mixing is 5 rpm, and the rotation speed of the third ball milling mixing is 5 rpm; the time of the first ball milling mixing is 2 h, the time of the second ball milling mixing is 24 h, and the time of the third ball milling mixing is 8 h.

[0132] The weight m1 of the first grinding medium, the weight m2 of the second grinding medium, and the weight m3 of the third grinding medium satisfy the relationship: m1:m2:m3=10:10:5.

[0133] The weight m4 of polyethylene glycol, the weight m5 of yttrium oxide and the weight m6 of the organic solvent satisfy the relationship:

[0134] m4:m5:m6=0.15:2.5:45.85.

[0135] The total weight m7 of the aluminum nitride powder and the weight m8 of the silane coupling agent satisfy the relationship: m7:m8=50:1.5.

[0136] The viscosity of the mixed slurry was 47 cP.

[0137] Comparative Example 2

[0138] Based on the contents disclosed in Example 1, the following modifications are further made:

[0139] The rotation speed of the first ball milling mixing is 2 rpm, the rotation speed of the second ball milling mixing is 2 rpm, and the rotation speed of the third ball milling mixing is 2 rpm; the time of the first ball milling mixing is 3 h, the time of the second ball milling mixing is 30 h, and the time of the third ball milling mixing is 10 h.

[0140] The weight m1 of the first grinding medium, the weight m2 of the second grinding medium, and the weight m3 of the third grinding medium satisfy the relationship: m1:m2:m3=10:10:5.

[0141] The weight m4 of polyethylene glycol, the weight m5 of yttrium oxide and the weight m6 of the organic solvent satisfy the relationship:

[0142] m4:m5:m6=0.165:2.75:39.885.

[0143] The total weight m7 of the aluminum nitride powder, the weight m8 of the silane coupling agent, and the weight m9 of the adhesive satisfy the relationship:

[0144] m7:m8:m9=55:0.55:1.65.

[0145] The silane coupling agent is XY-565 type coupling agent.

[0146] The viscosity of the mixed slurry was 118 cP.

[0147] Comparative Example 3

[0148] Based on the contents disclosed in Example 1, the following modifications are further made:

[0149] The rotation speed of the first ball milling mixing was 15 rpm, the rotation speed of the second ball milling mixing was 15 rpm, and the rotation speed of the third ball milling mixing was 15 rpm; the time of the first ball milling mixing was 4 h, the time of the second ball milling mixing was 60 h, and the time of the third ball milling mixing was 12 h.

[0150] The weight m1 of the first grinding medium, the weight m2 of the second grinding medium, and the weight m3 of the third grinding medium satisfy the relationship: m1:m2:m3=10:10:5.

[0151] The weight m4 of polyethylene glycol, the weight m5 of yttrium oxide and the weight m6 of the organic solvent satisfy the relationship:

[0152] m4:m5:m6=0.8:3.0:33.82.

[0153] The total weight m7 of the aluminum nitride powder, the weight m8 of the silane coupling agent, and the weight m9 of the adhesive satisfy the relationship:

[0154] m7:m8:m9=60:1.2:1.8.

[0155] The silane coupling agent is XY-350 type coupling agent.

[0156] The viscosity of the mixed slurry was 213 cP.

[0157] Comparative Example 4

[0158] Based on the contents disclosed in Example 3, the following modifications are further made:

[0159] Instead of using a grinding and mixing method, a water bath stirring method is used, and the water bath stirring includes a first water bath stirring, a second water bath stirring and a third water bath stirring. The temperature of the first water bath stirring is 70°C, the temperature of the second water bath stirring is 70°C, and the temperature of the third water bath stirring is 70°C; the rotation speed of the first water bath stirring is 200rpm, the rotation speed of the second water bath stirring is 200rpm, and the rotation speed of the third water bath stirring is 200rpm; the time of the first water bath stirring is 1h, the time of the second water bath stirring is 6h, and the time of the third water bath stirring is 1h.

[0160] The viscosity of the mixed slurry was 438 cP.

[0161] Related experiments and effect data:

[0162] The particle size and hydrolysis resistance of the spherical hydrolysis-resistant aluminum nitride granulated powder obtained in the example and the comparative example are shown in Table 1.

[0163] Table 1 Particle size and hydrolysis resistance of spherical hydrolysis-resistant aluminum nitride granulated powders of various embodiments and comparative examples

[0164]

[0165] As can be seen from Table 1, the hydrolysis resistance test of the spherical resistant aluminum nitride granulated powder is as follows: the spherical resistant aluminum nitride granulated powder is stirred in a 70°C water bath, and the pH value of the hydrolyzate is measured using pH test paper to observe the start of hydrolysis of the aluminum nitride granulated powder.

[0166] The present application provides a method for preparing a hydrolysis-resistant aluminum nitride granulated powder. The hydrolysis-resistant aluminum nitride granulated powder obtained by the preparation method can resist hydrolysis for more than 20 hours under 70°C water bath conditions. This may be because the weight m8 of the silane coupling agent and the weight m11 of the hydrolysis-resistant aluminum nitride granulated powder in the preparation method satisfy the relationship: m8:m11≥1.5:100, so that the hydrolysis-resistant aluminum nitride granulated powder has a sufficient amount of silane coupling agent, and the sufficient amount of silane coupling agent can be completely coated on the surface of the aluminum nitride powder particles. In the subsequent spray granulation stage, the silane coupling agent and the binder will be solidified together on the surface of the aluminum nitride powder particles, which can hinder the hydrolysis reaction between water and the aluminum nitride powder particles.

[0167] In summary, the embodiment of the present application provides a method for preparing a hydrolysis-resistant aluminum nitride granulated powder. The preparation method can fully deagglomerate the soft agglomerates of aluminum nitride powder through ball milling mixing modification. In addition, during the ball milling mixing process, the grinding balls will collide with the aluminum nitride powder to generate energy. The energy generated by these collisions can cause the silane coupling agent to be firmly and evenly anchored on the surface of the aluminum nitride powder particles, thereby improving the hydrolysis resistance of the aluminum nitride powder.

[0168] In addition, the preparation method of a hydrolysis-resistant aluminum nitride granulated powder provided in an embodiment of the present application organically unifies the modified aluminum nitride powder by organic coating with a silane coupling agent and spray granulation. On the basis of not increasing the complexity of the treatment process, the silane coupling agent can be first coated on the surface of the primary particles of aluminum nitride, thereby enabling the primary particles of aluminum nitride to have good hydrolysis resistance. Then, the primary particles of aluminum nitride with hydrolysis resistance are bonded by a binder. Through the spray granulation method, the separation and recovery of the organic solvent is realized, and the drying, curing and molding of the aluminum nitride granulated powder are realized.

[0169] In addition, the embodiment of the present application provides a method for preparing hydrolysis-resistant aluminum nitride granulated powder, which has the advantages of easy operation, low production cost and strong portability.

[0170] In addition, the embodiment of the present application provides a hydrolysis-resistant aluminum nitride granulated powder. When the hydrolysis-resistant aluminum nitride granulated powder is used to make ceramic structural parts, it can ensure that the ceramic structural parts have higher thermal conductivity, density and bending strength.

[0171] The above is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. It will be apparent to those skilled in the art that various modifications to these embodiments are possible, and the general principles defined in the present application can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to these embodiments shown in the present application, but will conform to the widest scope consistent with the principles and novel features applied for by the present application.

Claims

1. A method for preparing hydrolysis-resistant aluminum nitride granulated powder, characterized in that: The preparation method comprises: Performing a first ball milling to mix polyethylene glycol, yttrium oxide and an organic solvent to obtain a first mixture; Performing a second ball milling mixing of aluminum nitride powder, silane coupling agent and the first mixture to obtain a second mixture; The binder and the second mixture are mixed by a third ball milling process to obtain a mixed slurry; Screening the mixed slurry to obtain a filtrate; The filtered material is subjected to spray granulation to obtain spherical hydrolysis-resistant aluminum nitride granulated powder; The rotation speeds of the first ball milling, the second ball milling and the third ball milling are 5 rpm to 10 rpm respectively, and the time of the second ball milling>the time of the third ball milling>the time of the first ball milling.

2. The preparation method according to claim 1, characterized in that: The first ball milling mixing time is 2 hours to 4 hours, the second ball milling mixing time is 30 hours to 50 hours, and the third ball milling mixing time is 8 hours to 12 hours.

3. The preparation method according to claim 1, characterized in that: The grinding media used for the first ball milling mixture, the second ball milling mixture and the third ball milling mixture respectively include the first grinding medium, the second grinding medium and the third grinding medium, the particle size of the first grinding medium is 37mm~43mm, the particle size of the second grinding medium is 27mm~33mm, and the particle size of the third grinding medium is 17mm~23mm.

4. The preparation method according to claim 3, characterized in that: The weight m1 of the first grinding medium, the weight m2 of the second grinding medium and the weight m3 of the third grinding medium satisfy the relationship: m1:m2:m3=(16-18):(11-13):(8-10).

5. The preparation method according to claim 1, characterized in that: The weight m4 of the polyethylene glycol, the weight m5 of the yttrium oxide and the weight m6 of the organic solvent satisfy the relationship: m4:m5:m6=(0.15-0.18):(2.5-3.0):(31-44).

6. The preparation method according to claim 1, characterized in that: The total weight m7 of the aluminum nitride powder, the weight m8 of the silane coupling agent and the weight m9 of the adhesive satisfy the relationship: m7:m8:m9=(50-60):(1.5-2.4):(1.5-3.6).

7. The preparation method according to claim 1 or 6, characterized in that: The silane coupling agent comprises at least one of the following: KH-580 coupling agent, XY-565 coupling agent and XY-350 coupling agent; and / or The organic solvent includes anhydrous ethanol; and / or, The adhesive includes polyvinyl butyral.

8. The preparation method according to claim 1, characterized in that: The particle size D50 of the aluminum nitride powder is 1 μm to 2 μm, and the weight content m10 of oxygen in the aluminum nitride and the total weight m7 of the aluminum nitride powder satisfy the relationship: m10:m7<1:

100.

9. The preparation method according to claim 1, characterized in that: The viscosity of the mixed slurry is 60 cP to 200 cP.

10. A hydrolysis-resistant aluminum nitride granulated powder, characterized in that: The hydrolysis-resistant aluminum nitride granulated powder is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Injection molding method for nano aluminum nitride ceramics

    CN104844220A

  • Spherical large particle aluminum nitride powder preparation method

    CN104909762A

  • Preparation method of aluminum nitride powder used for heat conduction filler

    CN106586983A

  • Preparation method of coated aluminum nitride powder and prepared aluminum nitride ceramic substrate

    CN113185303A

  • Production of aluminum nitride green sheet

    JP1995267742A

Cited By

  • Normal-temperature stable / temperature-rising hydrated micro-powder binder and preparation method thereof

    CN119977602A